Cascade of parametric resonances in coupled Josephson junctions - Shukrinov, Yu.M.; Azemtsa-Donfack, H.; Rahmonov, I.R.; Botha, A.E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
We found that the coupled system of Josephson junctions under external electromagnetic radiation demonstrates a cascade of parametric instabilities. These instabilities appear along the IV characteristics within bias current intervals corresponding to Shapiro step subharmonics and lead to charging in the superconducting layers. The amplitudes of the charge oscillations increase with increasing external radiation power. We demonstrate the existence of longitudinal plasma waves at the corresponding bias current values. An essential advantage of the parametric instabilities in the case of subharmonics is the lower amplitude of radiation that is needed for the creation of the longitudinal plasma wave. This fact gives a unique possibility to create and control longitudinal plasma waves in layered superconductors. We propose a novel experiment for studying parametric instabilities and the charging of super-conducting layers based on the simultaneous variation of the bias current and radiation amplitude.